Workplace violence against doctors in China: A case analysis of the Civil Aviation General Hospital incident - Xiao, Yu; Du, Na; Chen, Jia; Li, Ya-lan; Qiu, Qin-ming; Zhu, Shao-yi (Frontiers in Public Health, 2022)
Background: Violence against health professionals is a global public health problem. In 2019, a doctor was killed in Civil Aviation General Hospital(CAGH), which triggered national discussion about hospital violence. Sina Weibo, the Chinese version of Twitter, played an important role in this public discussion. The CAGH incident provides us with an opportunity to explore how social media was used in the discussion on violence against health professionals. Methods: A data-set of Chinese-language micro-blogs was established by using the built-in search engine of Sina Weibo. Three key phrases, Civil Aviation General Hospital ("民航总医院"), doctor ("医生"), and knife ("刀") were used to search relevant micro-blogs between. We analyzed the content of the selected micro-blogs to examine: users' demographics, views about the incident of CAGH, and measures to prevent hospital violence. Results: 92.6% of micro-blogs were posted by individual users, and there were almost no legal professionals. 88.1% of micro-blogs expressed sympathy for the attacked doctor. Nearly half of micro-blogs showed disappointment with the government or society, and 59.2% of medical staff users expressed regret for engaging in medical work. Only 11.9% of micro-blogs put forward practical suggestions to prevent hospital violence. Conclusions: Social media is an important tool for gauging reaction to health events. However, the legal views were inadequately reflected in the debate, and constructive measures were rarely mentioned. Medical staff were worried about their occupational safety. Violence against health professionals remains extremely worrying, and all health professionals and relevant managers must actively deal with this problem in a comprehensive way.